2017
DOI: 10.4012/dmj.2016-303
|View full text |Cite
|
Sign up to set email alerts
|

Effects of experimental pastes containing surface pre-reacted glass ionomer fillers on inhibition of enamel demineralization

Abstract: This study aimed to evaluate the inhibitory effect of experimental pastes containing surface pre-reacted glass ionomer (S-PRG) fillers on enamel demineralization. Bovine blocks were treated twice a day for 4 days by 7 groups; experimental pastes containing 0-30 wt% S-PRG filler (S00, S01, S05, S10, and S30), deionized water (DW) as negative control, and NaF paste (MP) as positive control. The surfaces were demineralized by acetic acid for 3 days. Mineral loss (ML) was calculated by micro-computed X-ray tomogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 39 publications
2
19
0
Order By: Relevance
“…In addition, nearly one-third of the final concentration of Sr (i.e., 2,880 ppm) was incorporated after 1 h of immersion. Fast Sr absorption was previously reported by Nakamura et al 14) ; in that report, slight Sr adsorption occurred on the bulk enamel surface after less than 1 h of contact with an S-PRG containing experimental toothpaste. In the present study, Sr ions were supplied in S-PRG filler eluate; enamel powder was used as the test substance; therefore, Sr incorporation occurred more rapidly than in the report by Nakamura et al In addition, rapid incorporation of other ions (e.g., Al and borate) was observed, similar to that of Sr after 1 h of immersion for the S-PRG eluate.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…In addition, nearly one-third of the final concentration of Sr (i.e., 2,880 ppm) was incorporated after 1 h of immersion. Fast Sr absorption was previously reported by Nakamura et al 14) ; in that report, slight Sr adsorption occurred on the bulk enamel surface after less than 1 h of contact with an S-PRG containing experimental toothpaste. In the present study, Sr ions were supplied in S-PRG filler eluate; enamel powder was used as the test substance; therefore, Sr incorporation occurred more rapidly than in the report by Nakamura et al In addition, rapid incorporation of other ions (e.g., Al and borate) was observed, similar to that of Sr after 1 h of immersion for the S-PRG eluate.…”
Section: Discussionsupporting
confidence: 71%
“…Surface pre-reacted glass-ionomer (S-PRG) fillers release multiple ions (e.g., fluoride, borate, silicate, aluminum, sodium, and strontium) 5) ; various bioactive effects by these released ions have been reported for the suppression of bacterial adhesion [6][7][8][9] , biofilm formation 10,11) , prevention of demineralization [12][13][14] , and enhancement of remineralization 15,16) . As noted above, Sr and F ions are expected to provide a preventive effect with respect to caries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…FL‐BF is a multi‐ion releasing adhesive/composite restoration formed from FL‐Bond II and Beautifil Flow F10. Both FL‐Bond II and Beautifil Flow F10 contain S‐PRG fillers, which have a potential to release multi‐ions, such as F − , Al 3+ , BO33, Na + , SiO32SiO 3 2− , and Sr 2+ and to inhibit demineralization . It has been reported that the S‐PRG filler exerts a strong buffering capacity, bringing the pH value of the surrounding environment to a weak alkaline range when it comes into contact with water or acidic solution .…”
Section: Discussionmentioning
confidence: 99%
“…Specimens were then immersed in 125 mL of a buffered demineralizing solution containing 2.2 mmol/L CaCl 2, 2.2 mmol/L NaH2PO4, and 50 mmol/L acetic acid adjusted to pH 4.5 22) , then removed from the solution after 7 days demineralization, rinsed, after which µCT scanning was performed (Fig. 1).…”
Section: Specimen Preparationmentioning
confidence: 99%